Toxic tides of change: Ocean pollution as a cultural tipping point - Jessica M. Vandenberg; Eliana Ritts; Yoshitaka Ota; Russell Fielding (Ambio, 2026)
This paper offers a new perspective on the valuation of the impacts of industrial ocean pollution. Rising levels of industrial pollutants have a profound impact on marine resource-dependent peoples, particularly those dependent on seafood consumption. We argue that current regulation of these pollutants is both insufficient and inequitable, as it only accounts for impacts on physical health while ignoring cultural implications. This paper introduces the “cultural tipping point” as a new framework that integrates the impacts of ocean pollution on peoples’ physical and cultural health and well-being. Drawing on anthropology, marine sciences, public health, and critical Indigenous studies, the cultural tipping point synthesizes diverse concepts of “cultural keystone species,” food sovereignty, and industrial pollution. Ultimately, our goal is to make the cultural impacts of ocean pollution legible within global governance networks, and to advocate for greater allocation of societal resources to address this issue.

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

Observations of southern right whales ( Eubalaena australis ) surface feeding on krill in austral winter at South Georgia - Susannah V. Calderan; Tracey Dornan; Sophie Fielding; Ryan Irvine; Jennifer A. Jackson; Russell Leaper; Cecilia M. Liszka; Paula A. Olson; Martin A. Collins (Marine Mammal Science, 2023)

Feeding Ecology of Elusive Caribbean Killer Whales Inferred From Bayesian Stable Isotope Mixing Models and Whalers’ Ecological Knowledge - Jeremy J. Kiszka; Michelle Caputo; Paula Méndez-Fernandez; Russell Fielding (Frontiers in Marine Science, 2021)
Investigating the feeding ecology of marine predators is critical for understanding their roles and functional importance in ecosystems. However, assessing the diet of large and wide-ranging predators can be challenging, particularly in the case of rare and elusive species. Killer whales ( Orcinus orca ) are large apex predators in global oceans, but very little is known about their feeding ecology in tropical ecosystems, particularly in the Caribbean Sea. Killer whales are distributed throughout the Caribbean, and are a regular target of artisanal whalers in St. Vincent and the Grenadines (West Indies). Here we investigate the feeding ecology of Caribbean killer whales using a combination of stable isotope analysis (δ 15 N, δ 13 C) and traditional ecological knowledge (TEK) data from whalers operating from St. Vincent. Potential prey data from the Caribbean region included large pelagic teleosts, sea turtles, oceanic sharks, cetaceans, and oceanic cephalopods. Mixing models suggest that the contribution of odontocete cetaceans to the diet of killer whales is the most important (overall mean contribution: 60.4%), particularly mesopelagic delphinids ( Lagenodelphis hosei ; 26.4%, SD = 0.14), large teuthophageous odontocetes ( Physeter macrocephalus , Globicephala macrorhynchus ; 20.0%, SD = 0.14), and epipelagic delphinids ( Stenella attenuata ; 14%, SD = 0.14). Oceanic sharks ( Carcharhinus longimanus ) had a contribution of 17.0% of the diet of killer whales (SD = 0.13), and other potential prey had a relatively marginal contribution. TEK data suggest that whalers believe killer whales feed almost exclusively on cetaceans, particularly odontocete species that they hunt (e.g., G. macrorhynchus ). Stable isotope and TEK data were consistent to some extent, although TEK data are qualitative and based on a limited number of observations. Despite some limitations (including sample size for both methods), this study highlights the value of combining independent data sources and methodologies to investigate the ecological roles of marine predators in data-poor regions.

Artisanal and Aboriginal Subsistence Whaling in Saint Vincent and the Grenadines (Eastern Caribbean): History, Catch Characteristics, and Needs for Research and Management - Russell Fielding; Jeremy J. Kiszka (Frontiers in Marine Science, 2021)
Whaling has been a contentious international environmental issue for decades and carries complex ecological and socioeconomic implications. In Saint Vincent and the Grenadines (SVG), a small archipelagic nation located in the Eastern Caribbean, present-day whaling traces its origin to local interaction with American-based whalers during the nineteenth and early twentieth centuries. When American whaling in the region ceased, local shore-based whaling arose to fill the niche and to exploit the remaining, though diminished, stocks of large whales, as well as stocks of small cetaceans that the American whalers had not targeted as heavily. After a period of expansion throughout the late nineteenth and early twentieth centuries, which saw shore-whaling operations established on at least 11 islands in the region, Eastern Caribbean whaling experienced a period of attrition, during which most local whaling operations ceased. Two operations, both based in SVG, continue regularly today. This paper reviews the past and present status of whaling activities in SVG from the literature and using recent data collected from 2007 to 2017 through logbook data, interview surveys, and ethnographic observations. Small cetacean captures have been documented since 1949, and at least 15 species of odontocetes have been captured (primarily delphinids). From 1949 to 2017, a total of 13,856 small cetacean captures has been recorded, including 5,896 short-finned pilot whales ( Globicephala macrorhynchus ), 109 killer whales ( Orcinus orca ), and 7,851 other small cetaceans. Small cetacean catch records are largely incomplete and total catch estimates could not be attempted. Reliable abundance estimates do not exist. Consistent records for the take of large whales are only available for the period 1986–2020, during which 45 humpback whales ( Megaptera novaeangliae ) and 2 Bryde’s whales ( Balaenoptera edeni ) were taken. Additionally, 8 sperm whale ( Physeter macrocephalus ) captures were reported from 1967 and 1974. We also review whaling practices, existing national policy on whaling, management techniques outside of formal policy regimes, research needs, and future management perspectives. Future monitoring and management of whaling activities in SVG are strongly needed to assess the sustainability of small cetacean exploitation.

Oceanographic barriers, divergence, and admixture: Phylogeography and taxonomy of two putative subspecies of short‐finned pilot whale - Amy M. Van Cise; Robin W. Baird; Charles Scott Baker; Salvatore Cerchio; Diane Claridge; Russell Fielding; Brittany Hancock‐Hanser; Jacobo Marrero; Karen K. Martien; Antonio A. Mignucci‐Giannoni; Erin M. Oleson; Marc Oremus; et al. (Molecular Ecology, 2019)
Genomic phylogeography plays an important role in describing evolutionary processes and their geographic, ecological, or cultural drivers. These drivers are often poorly understood in marine environments, which have fewer obvious barriers to mixing than terrestrial environments. Taxonomic uncertainty of some taxa (e.g., cetaceans), due to the difficulty in obtaining morphological data, can hamper our understanding of these processes. One such taxon, the short‐finned pilot whale, is recognized as a single global species but includes at least two distinct morphological forms described from stranding and drive hunting in Japan, the “Naisa” and “Shiho” forms. Using samples ( n = 735) collected throughout their global range, we examine phylogeographic patterns of divergence by comparing mitogenomes and nuclear SNP loci. Our results suggest three types within the species: an Atlantic Ocean type, a western/central Pacific and Indian Ocean (Naisa) type, and an eastern Pacific Ocean and northern Japan (Shiho) type. mtDNA control region differentiation indicates these three types form two subspecies, separated by the East Pacific Barrier: Shiho short‐finned pilot whale, in the eastern Pacific Ocean and northern Japan, and Naisa short‐finned pilot whale, throughout the remainder of the species' distribution. Our data further indicate two diverging populations within the Naisa subspecies, in the Atlantic Ocean and western/central Pacific and Indian Oceans, separated by the Benguela Barrier off South Africa. This study reveals a process of divergence and speciation within a globally‐distributed, mobile marine predator, and indicates the importance of the East Pacific Barrier to this evolutionary process.

Species composition of coastal dune vegetation in Scotland has proved resistant to climate change over a third of a century - Robin J. Pakeman; Jim Alexander; Joan Beaton; Rob Brooker; Roger Cummins; Antonia Eastwood; Debbie Fielding; Julia Fisher; Sarah Gore; Richard Hewison; Russell Hooper; Jack Lennon; et al. (Global Change Biology, 2015)
Climate change is expected to have an impact on plant communities as increased temperatures are expected to drive individual species' distributions polewards. The results of a revisitation study after c. 34 years of 89 coastal sites in Scotland, UK, were examined to assess the degree of shifts in species composition that could be accounted for by climate change. There was little evidence for either species retreat northwards or for plots to become more dominated by species with a more southern distribution. At a few sites where significant change occurred, the changes were accounted for by the invasion, or in one instance the removal, of woody species. Also, the vegetation types that showed the most sensitivity to change were all early successional types and changes were primarily the result of succession rather than climate‐driven changes. Dune vegetation appears resistant to climate change impacts on the vegetation, either as the vegetation is inherently resistant to change, management prevents increased dominance of more southerly species or because of dispersal limitation to geographically isolated sites.